The effects of small-scale coastal development on the eelgrass (Zostera marina L.) distribution along the Swedish west coast – Ecological impact and legal challenges. (1st November 2017) - Eriander, Louise; Laas, Kristjan; Bergström, Per; Gipperth, Lena; Moksnes, Per-Olav
Abstract: Anthropogenic impacts on coastal areas have led to an increased degradation of marine environments globally. Eelgrass ecosystems are particularly susceptible to human induced stressors as they are sensitive to low light conditions and usually grow in shallow protected areas where pressure from coastal development is high. The extensive decline in coverage of eelgrass along the Swedish Northwest coast since the 1980s has largely been attributed to the effects of coastal eutrophication and overfishing. However, the impact on eelgrass from small-scale coastal development (docks and marinas) has never been investigated in this area. The aim of this study was to assess the local and large-scale effect of shading by docks and marinas on eelgrass habitats along the Swedish NW coast and to investigate the decision process behind small-scale exploitation to identify problems with the current legislation, which allows for continued exploitation of eelgrass. Through field assessments of eelgrass around docks and analysis of available data on eelgrass and dock distribution along the coast, the present study demonstrates that shading from docks reduced eelgrass coverage with on average 42–64% under and adjacent to the docks, and that floating docks affected larger areas and caused a much stronger reduction in eelgrass coverage (up to 100% loss) compared to docks elevated on poles (up to 70% reduction in coverage). The total eelgrass area negatively affected by docks and marinas along the NW coast was estimated to approximately 480 ha, an area corresponding to over 7% of the present areal coverage of eelgrass in the region. The analysis of decisions for dock construction showed that eelgrass was generally not assessed or considered in the decision process and that 69–88% of the applications were approved also in areas where eelgrass was present. Furthermore, marine protected areas only marginally reduced the approval of applications in eelgrass habitats. The continued small-scale development along the Swedish NW coast constitutes a significant threat to the already decimated coverage of eelgrass along the coast and changes in the management practices are needed in order to achieve both national and international goals on environmental status. Highlights: Shading from docks reduced eelgrass coverage with 42–64% within 6 m from docks. Floating docks had 50% larger negative impact compared to elevated docks. 480 ha of eelgrass habitat is negatively affected by dock shading in NW Sweden. Eelgrass was rarely assessed or considered within dock applications and decisions. 69% of dock applications with eelgrass, inside protected areas were approved.